Opportunities and Threats for City Logistics Development from a Local Authority Perspective - Maja Kiba-Janiak (Journal of Economics and Management, 2017)
Aim/purpose - The main purpose of the paper is the identification of opportunities and threats for city logistics development from a local authority perspective. Design/methodology/approach - The paper presents the original results of surveys conducted among city logistics experts from all over the world and among representa- tives of twelve EU capital cities. Findings - According to the study the most important opportunities for cities are stakeholders' willingness for cooperation, as well as a good and long cooperation with them. It shows that a local authority cannot introduce any solutions in the field of city logistics without cooperating with other stakeholders. Therefore, the lack of cooperation can be a threat. The other threat highlighted by the majority of studied cities is the lack of standards on data collections. Without information in real time on problems and activities undertaken by various stakeholders in the field of city logistics it is very difficult for strategic and tactical decisions to be made by a local authority. Research implications/limitations - The most significant limitation of the research was the sample of respondents. Despite the fact that the questionnaire was sent to 28 EU capital cites only 12 out of them have completed and returned the questionnaire. A further problem arises from the lack of standards on collecting information on city logistics by cities. As a result of it many European cities do not collect this information or do it in a fragmentary way. Originality/value/contribution - The research results introduced in the paper make a contribution to the theoretical and practical knowledge on city logistics development. It fills the gap related to the external factors affecting the development of city logistics. The author's concept of the framework for city logistics development with the inclusion of threats and opportunities and the set of questions can be a useful tool for local authorities as well as enriching the theoretical background for city logistics strategic planning.